Effect of facet-joint degeneration on the in vivo motion of the lower lumbar spine - Yin, Jun (J Orthop Surg Res, 2020)
OBJECTIVE: This research studied the in vivo motion characteristics of the L3–S1 lumbar spine with facet-joint degeneration during functional activities. METHODS: Thirteen male and 21 female patients with facet-joint degeneration at the L3–S1 spinal region were included in the study. The L3–S1 lumbar segments of all the patients were divided into 3 groups according to the degree of facet-joints degeneration (mild, moderate, or severe). The ranges of motion (ROM) of the vertebrae were analyzed using a combination of computed tomography and dual fluoroscopic imaging techniques. During functional postures, the ROMs were compared between the 3 groups at each spinal level (L3–L4, L4–L5, and L5–S1). RESULTS: At L3–L4 level, the primary rotations between the mild and moderate groups during left-right twisting activity were significantly different. At L4–L5 level, the primary rotation of the moderate group was significantly higher than the other groups during flexion-extension. During left-right bending activities, a significant difference was observed only between the moderate and severe groups. At L5–S1 level, the rotation of the moderate group was significantly higher than the mild group during left-right bending activity. CONCLUSIONS: Degeneration of the facet joint alters the ROMs of the lumbar spine. As the degree of facet-joint degeneration increased, the ROMs of the lumbar vertebra that had initially increased declined. However, when there was severe facet-joint degeneration, the ROMs of the lumbar spine declined to levels comparative to the moderate group. The relationship between the stability of the lumbar vertebra and the degree of facet-joint degeneration requires further study.